The Effect of Addition of Used Styrofoam on the Characteristics of Asphalt Physical Properties - Barus, Diana Alemin (Talenta Publisher, 2020)
Styrofoam had many purposes, especially for the safety of electronic objects, because it is light, durable and strong. The volume of styrofoam is enormous, reaching 30% of total waste in the world. Therefore, it causes problems if disposed of and it will become a very inconvenient waste and it can undermine the environment. This study aims to determine the effect of adding former styrofoam waste to asphalt on the characteristics of the 60/70 pen asphalt. The sample was made by melting the Styrofoam with Xylene then putting it in heated asphalt and then stirring it evenly. Next, Styrofoam enters the material into the sample container and then is refrigerated outside for 1 hour. After that, the sample is immersed in water for 3 hours. The sample meets the asphalt requirements test for each sample including penetration test, softening point, flash point, burning point, density, and ductility. This shows that the higher the concentration, the addition of styrofoam mixed with asphalt resulted in conversion and increased performance of the mixture. While at density, it appears that the addition of Styrofoam results in a lower density value.